It takes (at least) two to tango: Comparing the affordances of two learner mistreatment reporting mechanisms - Rachul, Christen; Garber, Jesse; Hamilton, Joanne; Squires, Anitra; Porhownik, Nancy; Gruber, Jackie; Jacobsohn, Eric (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2026)
Background: The affordances, or characteristics, of learner mistreatment reporting mechanisms can shape the information elicited from these mechanisms, which has an impact on how institutions understand the scope and nature of learner mistreatment. This study compares whether and how the affordances of two mistreatment reporting mechanisms elicit different information about learner mistreatment at a single institution.Methods: We conducted an interpretive content analysis of reports submitted using two mechanisms, one that elicits reports through end-of-rotation evaluations and one through a voluntary web-based system, between July 2015 and December 2021. We extracted the metadata from reports and applied a coding framework informed by the Healthcare Complaints Analysis Tool (HCAT) to the narrative descriptions in reports. Data analysis included descriptive statistics and the chi-square test on SPSS v.27.Results: We collected 90 elicited reports and 240 voluntary reports of mistreatment. Similar types of mistreatment were reported through each mechanism, but disrespectful behaviour and bias and discrimination were reported significantly more in voluntary reports. Elicited reports most frequently included incidents of learner mistreatment in clinical settings, whereas voluntary reports included incidents from a wide variety of settings and people or were issues other than mistreatment.Discussion: Utilizing multiple learner mistreatment reporting mechanisms with different affordances can mitigate the limitations of a single mechanism, help identify a more nuanced understanding of learner mistreatment, and increase reporters’ choices for how and when to report mistreatment. Increased information allows an institution to address specific incidents and develop targeted, preventive educational activities and faculty development.